The Role of Canva-Based Learning Media in Improving Mathematical Critical Thinking Skills in Elementary School Students’ Data Analysis Material - Nur Afiah; Ety Mukhlesi Yeni; Aminah Aminah (FKIP - Universitas Riau, 2026)
The development of digital technology provides opportunities for teachers to create more interactive and engaging learning experiences. This study aims to determine the effectiveness of Canva-based interactive learning media in improving fifth-grade students’ Mathematical Critical Thinking skills in data analysis material. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent comparison-group design involving a control class and an experimental class. Data were collected through pretest and posttest instruments. The results showed that the experimental class experienced a significant increase in the average score, from 47.86 in the pretest to 70.00 in the posttest, indicating a substantial improvement compared to the control class. The data were analyzed using normality, homogeneity, and independent samples t-tests. The normality test results indicated that all data were normally distributed (Sig. > 0.05), while the homogeneity test showed equal variances between groups (Sig. = 0.733 > 0.05). Furthermore, the t-test result showed a significance value of 0.000 (< 0.05), indicating a significant difference between the two groups. These findings demonstrate that Canva-based interactive learning media is effective in enhancing students’ Mathematical Critical Thinking skills in elementary school data analysis learning.